Floristic Account of the Genus Lipocarpha R. Brown (Cyperaceae) - Shaikh , Rafeeque Ishakhoddin (Plantae Scientia, 2023)
Lipocarpha R. Br. (s.. str.) a small genus with over 15 species distributed through the world with high species concentration in Africa. In India it is represented with 5 species with the addition of 2 species namely L. raynaliana Govind. and L. redyii Hooper to the earlier recorded 3 species (Clarke, 1893). The genus Lipocarpha R. Br. (s. str.) is mainly characterised by the two hypogynous scales which are very thin hyaline lightly adhering to nuts together with the capitate inflorescence. Clarke (1893) has shown its affinity with the sec. Micranthae under Scirpus (= Rikliella J. Raynal). The hypogynous scales of Lipocarpha have been variously interpreted. (For detail see Bentham J. Uinn. Soc. Bot. 15:509-10 & 518.1877. Clarke in Tnislten Dyer Fl. Tropical Africa 8:468-69.1902, Kern, in Steenis Fl. Malesiana 1.7(3):521). The present report is hoped to provide basic material for further research in Cyperaceae.